Development and evaluation of a novel vaccine against prevalent invasive multi-drug resistant strains of Streptococcus pneumoniae - Bahy, Rehab H. (PeerJ, 2016)
Streptococcus pneumoniae is a pathogen that causes serious invasive infections, such as septicemia, meningitis and pneumonia in addition to mild upper respiratory tract infections. Protection from pneumococcal diseases is thought to be mediated mainly by serotype-specific antibodies to capsular antigens. Pneumococcal conjugate vaccine consists of sugars (polysaccharides) from the capsule of the bacterium S. pneumoniae that are conjugated to a carrier protein. Three pneumococcal conjugated vaccines, each directed against a group of serotypes, are registered in Egypt; however, local vaccine production is required to cover the most prevalent serotypes. In this work, capsular polysaccharide from the most current and prevalent serotypes in Egypt were extracted, purified and conjugated to bovine serum albumin (BSA). The polysaccharide protein conjugate was purified through ultrafiltration technique and molecular size distribution was compared to an available vaccine. The immunogenicity of the prepared vaccine was examined via two methods: First, by measuring the levels of the elicited antibodies in the sera of the vaccinated mice; second, by challenging the vaccinated groups of mice with approximately 10(7) CFU of each specific serotype and determining the degree of protection the developled vaccine offers. Our results show that the developed conjugated capsular polysaccharide vaccine is highly immunogenic and protective in mice. This finding illustrates the importance of tracking the most recent and predominant peneumococcal serotypes to generate effective vaccines, instead of using expensive imported vaccines with large number of serotypes which might not be even present in the community.